Effect of soaking with Gibberellic Acid (GA3) on seeds germination and Seedling quality of some varieties of pistachio - جرجس مخول ,; وفاء علي عطاف , (Latakia University Journal -Biological Sciences Series, 2023)
This research was carried out in the nursery of Tishreen University and the laboratories of the Faculty of Agriculture to study the effect of soaking seeds of several varieties of pistachios ("Abu Riha", "Ajami" and "Marawahi"), in different levels of gibberellic acid solution (GA3) on the germination percentage and the quality of resulted seedlings. The results show that; the soaking of seeds in different concentrations of GA3 for 24 hours led to an increase in the germination percentage of the seeds of the studied varieties "Abu Rayha", "Ajami" and "Marawahi". The percentages of germination varied according to the concentration used of GA3 and the variety studied. The treatment of soaking the seeds of the cultivar Abu Rayha at a concentration of 600 ppm gave the highest germination percentage (92.19%) and was significantly superior to the rest of the treatments, while the treatment of soaking the seeds of other both cultivars "Ajami" and "Marawhi" at a concentration of 400 ppm gave the highest germination percentage (64.07% and 38.02%), respectively. The best quality of the resulted seedlings (plant hight, main stem diameter and average seedling weight) was obtained for the studied cultivars when treated by soaking with 400 ppm GA3 solution for the variety "Abu Riha" 44.33 cm, 4.82 mm, 40.5 g) respectively, while the treatment with a concentration of 200 ppm for "Ajami" cultivar seeds had the best quality of the resulted seedlings in terms of plant hight (47.25 cm), main stem diameter (3.36 mm) and average seedling weight (40.6 g). The best quality of "Marawhi" variety seedlings was when using the GA3 concentration of 400 ppm, and the average seedling hight was (37.22 cm), with average weight of (42.0 g), while the average diameter of the seedling stem was (3.52 mm) at the level of 600 ppm of GA3.